The Relationship Between Religious Affiliation and Returns to Human Capital for Women1. Issue 3 (20th September 2013) - Kortt, Michael A.; Dollery, Brian; Grant, Bligh
<x xml:space="preserve">Abstract</x> This paper explores the relationship between wages and religious affiliation for Australian women using a human capital earnings function corrected for selectivity in labour force participation. Data drawn from the 2004, 2007, and 2010 waves of the Household Income Labour Dynamics Australia (HILDA) Survey were analysed for women between the age of 25 and 54. Our results indicate that women who identify as being Catholic benefit from a wage premium of 4.5 per cent relative to women who identify as being Anglican—the largest Protestant denomination in Australia—even after controlling for a range of demographic, social and economic characteristics. Potential explanations such as the attitude of women towards work and returns to education and experience do not appear to be major determinants of this wage‐differential. Thus, it appears other unobservable traits may be a key factor in explaining the observed Catholic wage premium.